Thalidomide induces clinical remission and mucosal healing in adults with active Crohn's disease: a prospective open-label study. (May 2017) - He, Yao; Mao, Ren; Chen, Fang; Xu, Ping-Ping; Chen, Bai-Li; Wu, Yun; Qiu, Yun; Zhang, Sheng-Hong; Feng, Rui; Zeng, Zhi-Rong; Ben-Horin, Shomron; Chen, Min-Hu
Background: Thalidomide is effective in inducing and maintaining clinical remission in children and adolescents with refractory Crohn's disease (CD). However, little is known about the efficacy and safety of thalidomide for adult patients with CD. Methods: We conducted a prospective open-label cohort study between January 2013 and April 2015. A total of 47 adult patients with active CD who were dependent/resistant or intolerant to corticosteroids and/or immunomodulators or biologics received 50–100 mg of thalidomide daily. Primary outcome was clinical remission evaluated at week 8. Endoscopic assessment was performed at week 24 and defined as endoscopic response (decrease in Crohn's Disease Endoscopic Index of Severity [CDEIS] score > 5 points from baseline CDEIS of 6 or more), complete endoscopic remission (CDEIS score < 3), and mucosal healing (MH) (no ulceration). Results: A total of 47 adults with active CD were enrolled. The clinical remission rate was 14.9% and 23.4% at week 4 and week 8, but increased to 46.8% at week 12 and 53.2% at week 24 out of all the 47 patients included (intention-to-treat analysis). Altogether 32 patients consented and underwent ileocolonoscopy at week 24. The rate of endoscopic response and complete endoscopic remission were 68.4% and 43.8%. MH (no ulceration) was achieved in 28.1% of patients. Adverse events occurred in 27/47 (57.4%) patients but necessitated therapy discontinuation in only 5/47 (10.6%) of patients. Conclusions: Low-dose thalidomide was effective and tolerated for inducing and maintaining clinical remission in adult patients with active CD, but the optimal time frame for thalidomide to induce clinical remission may be longer than previously appreciated and is probably optimal at 12 weeks. MH could reasonably be achievable with thalidomide.